How the Esther Network model for coproduction of person-centred health and social care was adopted and adapted in Singapore: a realist evaluation - Julian Thumboo; Johan Thor; Boel Andersson Gäre; Esther Li Ping Lim; Giat Yeng Khee; Monika Allgurin (BMJ Open)
Objectives The Esther Network (EN) model, a person-centred care innovation in Sweden, was adopted in Singapore to promote person-centredness and improve integration between health and social care practitioners. This realist evaluation aimed to explain its adoption and adaptation in Singapore.Design An organisational case study using a realist evaluation approach drawing on Greenhalgh et al (2004)’s Diffusion of Innovations in Service Organisations to guide data collection and analysis. Data collection included interviews with seven individuals and three focus groups (including stakeholders from the macrosystem, mesosystem and microsystem levels) about their experiences of EN in Singapore, and field notes from participant observations of EN activities.Setting SingHealth, a healthcare cluster serving a population of 1.37 million residents in Eastern Singapore.Participants Policy makers (n=4), EN programme implementers (n=3), practitioners (n=6) and service users (n=7) participated in individual interviews or focus group discussions.Primary and secondary outcome measures Outcome data from healthcare institutions (n=13) and community agencies (n=59) were included in document analysis.Results Singapore’s ageing population and need to transition from a hospital-based model to a more sustainable community-based model provided an opportunity for change. The personalised nature and logic of the EN model resonated with leaders and led to collective adoption. Embedded cultural influences such as the need for order and hierarchical structures were both barriers to, and facilitators of, change. Coproduction between service users and practitioners in making care improvements deepened the relationships and commitments that held the network together.Conclusions The enabling role of leaders (macrosystem level), the bridging role of practitioners (mesosystem level) and the unifying role of service users (microsystem level) all contributed to EN’s success in Singapore. Understanding these roles helps us understand how staff at various levels can contribute to the adoption and adaptation of EN and similar complex innovations systemwide.